Effective writing in English : a sourcebook. - Hannay, Mike, 1951-; Mackenzie, John Lachlan, 1950- (Bussum : Coutinho, 2002)
Deel 1 The three processes of writing 1. Planning 2. Writing proper 3. Editing Deel 2 Organizing the text 4. The title and the introduction 5. The body 6. The conclusion Deel 3 Constructing effective sentences 7. Clause combining 8. The order of information in the clause 9. Textual Cohesion 10. Punctuation Deel 4 Getting the details right 14. Matters of usage 15. Point of view 16. Forceful argumentation 17. Spelling guidelines 18. Usage notes for connectives 19. Referring to other texts 20. A checklist for revising and correcting
Keywords: Correspondentie -- Engels